2010
DOI: 10.1097/wnp.0b013e3181cb426d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corticosteroid Usage Combined With Multidrug Therapy on Nerve Damage Assessed Using Nerve Conduction Studies: A Prospective Cohort Study of 365 Untreated Multibacillary Leprosy Patients

Abstract: The purpose of this study is to determine the extent of nerve involvement and to study the effect of corticosteroids combined with multidrug therapy on nerve damage in leprosy patients using sensory and motor nerve conduction studies. A cohort of 365 untreated multibacillary leprosy patients were prospectively studied using sensory and motor nerve conduction studies on upper and lower limb nerves. They were subgrouped as those to be treated with 12-week regimen of corticosteroids for reaction and/or neuritis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 18 publications
3
22
1
4
Order By: Relevance
“…In this first prospective study investigating ultrasonographic nerve abnormalities in leprosy we found that the neural involvement may not improve after treatment, in accordance with the findings of previous clinical and electrophysiological studies [1719,2427]. Furthermore, US findings can worsen despite the operational classification and the presence of reactions, as demonstrated by the CSA increase in the CF nerve in PB and in patients without reactions and by the increased frequency of echogenicity abnormalities detected in the post-treatment evaluation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this first prospective study investigating ultrasonographic nerve abnormalities in leprosy we found that the neural involvement may not improve after treatment, in accordance with the findings of previous clinical and electrophysiological studies [1719,2427]. Furthermore, US findings can worsen despite the operational classification and the presence of reactions, as demonstrated by the CSA increase in the CF nerve in PB and in patients without reactions and by the increased frequency of echogenicity abnormalities detected in the post-treatment evaluation.…”
Section: Discussionsupporting
confidence: 89%
“…One previous prospective study [17] that investigated the electrophysiological parameters of 365 MB patients who were divided in two groups (with and without reactions) revealed that deterioration of nerve function was more frequent than improvement in both groups. Similar to the findings of Capadia et al, our results revealed high frequencies of poor outcomes for CSA (up to 25%) and echogenicity (45.2%) in the patients without reactions, sometimes with greater percentages of abnormalities than patients with reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this connection, nerve conduction studies (NCS) are a sensitive method for the investigation of PNL 13,28,30 (C). There is prominence of demyelinating neuropathy of the ulnar nerve at the elbow in 55.0% of the cases 34,36 (C). All these studies emphasize the asymmetric and multifocal impairments.…”
Section: Nerve Conduction Studies: Diagnostic Of Sensibility and Specmentioning
confidence: 99%
“…However, these effects did not persist after the interruption of the steroid treatment 55 (B). In a study where an initial dose of 40 mg/day was used and reduced in up to 12 months to 5 mg/day, with repetition of treatment if reactions appeared, it was observed impairment prevention and improvement of motor function during drug administration, but the sensory impairment did not show any function recovery 56 (C). The electrophysiological assessment of 24 PB PNL patients with neural loss, treated with an initial dose of 60 mg/day orally, which was progressively reduced for six months, presented significant sensory and motor improvements in the study period 29 (B).…”
Section: Studies On Prophylactic Treatment With Steroids Combined To mentioning
confidence: 99%